An Investigation of Student’s Problems in Writing Recount Text - Syafitri; Octasary, Magvirah; Hardianti; Ratna; Stenalt, Maria Hvid (Buletin Pengabdian Multidisiplin, 2023)
The aim of this research is to find out the problems written by the tenth-grade students of SMA Negeri 1 Sausu in writing recount text. This study concentrated on the issues students had when producing recount texts in terms of grammar, organization, content and vocabulary. The researcher applied descriptive qualitative research in this study. The subject of this research was the tenth-grade social students which consisted of 20 students. The instrument was test. In collecting the data, written test is used in order to know how the students understood in writing recount text and in addition to find out their problems in writing. There were 4 steps in collecting the data in this research. They are preparing research instrument, distributing the test instruction to students, collecting the data, and analyzing students’ writing. In order to determine the percentage and the most common mistakes that students made when producing recount texts, the researcher calculated the difficulties based on the classification. The results made it evident that most students had difficulty writing a recount paragraph. A student (4.5 percent) had extremely poor content, two students (9.09 percent) had extremely poor organization, ten students (45.4 percent) had extremely poor vocabulary and twelve students (54.5%) had extremely poor grammar. The majority of students found it difficult to comprehend how to use language in a recount text, which is why it happened. Additionally, they are inexperienced and lacked knowledge in writing recount texts.